2010
DOI: 10.1109/l-ca.2010.5
|View full text |Cite
|
Sign up to set email alerts
|

Synctium: a Near-Threshold Stream Processor for Energy-Constrained Parallel Applications

Abstract: Abstract-While Moore's law scaling continues to double transistor density every technology generation, supply voltage reduction has essentially stopped, increasing both power density and total energy consumed in conventional microprocessors. Therefore, future processors will require an architecture that can: a) take advantage of the massive amount of transistors that will be available; and b) operate these transistors in the near-threshold supply domain, thereby achieving near optimal energy/computation by bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…Errors introduced by process variation appear in the form of differences in delay for driven signals and input offset and delay for receiver circuits. However, because these errors are generally static in nature they can potentially be mitigated by embedded measurement and calibration circuits [23], localized adaptive body biasing and voltage scaling [38], or device and block sparing [39].…”
Section: Process Variationmentioning
confidence: 99%
“…Errors introduced by process variation appear in the form of differences in delay for driven signals and input offset and delay for receiver circuits. However, because these errors are generally static in nature they can potentially be mitigated by embedded measurement and calibration circuits [23], localized adaptive body biasing and voltage scaling [38], or device and block sparing [39].…”
Section: Process Variationmentioning
confidence: 99%
“…Research has shown that minimum energy is typically achieved when V dd enters the near/sub-threshold region, where about a 10× reduction in energy per computation is achievable [7]. In these cases, the impact of static variations become much more extreme and can be very difficult to predict in large CMOS dies [8].…”
Section: Static Variationsmentioning
confidence: 99%
“…These slower speeds lead designers to push sub-threshold processors to a more parallel approach. For example, in [8] the authors use multiple execution lanes to regain the throughput lost by the increased delays of sub-threshold operation. The following subsections will discuss the viability of the techniques under review to operate in the sub-threshold region.…”
Section: Error Detection and Recovery In The Sub/near-threshold Regimementioning
confidence: 99%
“…We explore the tradeoffs associated with timing speculation in the context of SIMD designs, and build on our earlier work [13], to develop and evaluate SIMD-and GPU-specific extensions to the timing speculation technique. In our initial work, we observed that naively applying timing speculation to a SIMD pipeline may perform poorly.…”
Section: Introductionmentioning
confidence: 99%